Basic principles of combination therapy: focus on drug-drug interaction - S. Yu. Martsevich; Yu. V. Lukina; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The article is devoted to the issue of drug interactions in the combination regimens. Today, when drug therapy is the first-line approach for patients with noncommunicable diseases, and the world population ageing leads to an increase in the number of patients with severe comorbidity and polypharmacy, the problem of drug-drug interaction is especially relevant. The article discusses the main types of drug interactions  — pharmacokinetic (related to absorption, distribution, metabolism and excretion of drugs) and pharmacodynamic ones, leading to synergy or antagonism of the pharmacological effects. The consequences of drug interactions can be desirable and undesirable, while the latter are much more common. Attention should be directed precisely to preventing such interactions. Also, using data from special scales and lists (Beers criteria, STOPP/START criteria), the options for various adverse drugdrug interactions are briefly described. In addition, the article provides a number of Internet resources that allow assessing the drug interaction risk when prescribing combination therapy.